English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

Solve the following system by substitution
3x – y = –7
x + y = –9

2007-04-28 17:31:20 · 8 answers · asked by Miss Mama 1 in Science & Mathematics Mathematics

8 answers

This sustem is easier to solve by addition, but evidently you have a sadistic teacher.

3x – y = –7 add y+7 to each side
3x+7=y
x + y = –9 substitute 3x+7 for y
x+3x+7=-9
4x+7=-9 subtract 7 from each side
4x=-16 divide both sides by 4
x=-4
3x+7=y substitute -4 for x
3*(-4)+7=y
y=7-12
y=-5
(-4, -5)

2007-04-28 17:38:34 · answer #1 · answered by yupchagee 7 · 9 0

Write the first equation as y = 3x + 7. Then
substitute y in the second equation with 3x + 7,
so we have x + (3x + 7) = -9, i.e. 4x = -16, i.e.
x = -4. Moreover, y = 3(-4) + 7 = -12 + 7 = -5.
Hence, x = -4 and y = -5 is the solution.

2007-04-29 00:35:47 · answer #2 · answered by I know some math 4 · 0 0

3x - y = -7 -----> equation (1)
x + y = -9 -----> equation (2)
from equation (2),
x = -9 - y -----> equation (3)
substitute equation (3) into equation (1)
3(-9 - y) - y = -7
expand out,
-27 - 3y - y = -7
-4y = -7 + 27
-4y = 20
4y = -20
therefore, y = -5.
to find x, substitute the value of y = -5 into equation 3
x = -9 - (-5)
therefore, x = -4.

2007-04-29 00:40:44 · answer #3 · answered by Anonymous · 0 0

3x - y = -7 (Eq. 1)
x + y = - 9 (Eq. 2)

x + y = - 9 (Eq. 2)
x = -9 - y (Eq. 3)
Substitute Eq. 3 in Eq. 1

3x - y = - 7 (Eq. 1)
3( - 9 - y) -y = - 7
-27 - 3y - y = -7
-4y - 27 + 27 = -7 + 27
-4y = 20
-4y/-4 = 20/-4
y = - 5 ===> Value of y

Subsitute the value of y in Eq. 2
x + y = -9 (Eq. 2)
x + (-5) = -9
x - 5 = - 9
x - 5 + 5 = - 9 + 5
x = - 4 ===> value of x
To check, substitute the value of x and y in Eq. 1
3x - y = - 7 (Eq. 1)
3(-4) - (-5) = - 7
-12 + 5 = - 7
-7 = - 7

2007-04-29 00:42:05 · answer #4 · answered by detektibgapo 5 · 0 0

From the first equation, you get...
x=-9-y

substitute this expression for x in the first equation...
3(-9-y)-y=-7
distribute...
-27-3y-y=-7
-4y=20
divide both sides by -4 and you get...
y=-5

plug in -5 for y in the second equation and get...
x-5=-9
x=-4

so the answer is
x=-4, y=-5
(-4,-5)

2007-04-29 00:37:24 · answer #5 · answered by YK 2 · 0 0

x + y = -9 becomes x = -9 -y.

Use this value of x in the first equation.

3(-9-y) - y = -7

-27 - 3y -y = -7
-3y -y = 20
-4y = 20
y = -5

Now find x:

x = -9 - (-5)
x = -9 + 5
x = -4

Check:

-4 + -5 = -9 (Bingo!)

2007-04-29 00:36:50 · answer #6 · answered by ZeroCarbonImpact 3 · 0 0

y = 3x + 7
x + 3x + 7 = - 9
4x = - 16
x = - 4
y = - 5

2007-04-29 07:38:47 · answer #7 · answered by Como 7 · 0 0

i used the following formula in order to correctly solve this problem:

3.14(x) = 466-(m)

happy solving!!!!

2007-04-29 00:39:09 · answer #8 · answered by waterlily750 4 · 0 0

fedest.com, questions and answers